POLICY EVALUATION OF EDUCATION ASSISTANCE THROUGH THE INDONESIA PINTAR PROGRAM (PIP) (AN EVALUATIVE STUDY: BASED ON THE REGULATION OF THE MINISTER OF EDUCATION AND CULTURE NUMBER 10 OF 2020 CONCERNING THE INDONESIA PINTAR PROGRAM) - Antonius; Dwi Suharnoko; Rocmad Efendy (PT. Antis International Publisher, 2026)
Objective: This study evaluates the implementation of the Indonesia Smart Program (Program Indonesia Pintar/PIP) in improving educational access for economically disadvantaged students. It examines the program's effectiveness in reducing school dropout risk and identifies the factors influencing its implementation. Method: A descriptive qualitative approach was employed. Data were collected through interviews, observations, and document analysis involving the school principal, teachers, PIP beneficiary students, and their parents at SDN 001 Barong Tongkok, West Kutai Regency. Data were analyzed using policy implementation dimensions, including communication, resources, implementers' disposition, organizational structure, implementation process, and targeting accuracy. Results: The findings indicate that the implementation of PIP at SDN 001 Barong Tongkok has generally been effective. The school successfully carried out program socialization, beneficiary identification, data verification, proposal submission, and assistance during fund disbursement. The financial assistance contributed to reducing students' risk of dropping out by supporting essential educational expenditures, including uniforms, school supplies, books, and transportation-related needs. Program implementation was strengthened by effective communication, committed implementers, clear administrative procedures, and reliable beneficiary data. However, several challenges remain, including delayed information dissemination, incomplete administrative documents, and the exclusion of some eligible students from receiving assistance. Novelty: This study provides an empirical policy evaluation of the Indonesia Smart Program at the school implementation level by integrating policy implementation dimensions with beneficiary targeting accuracy. The findings offer practical evidence for improving educational assistance policies through more accurate beneficiary identification, continuous data updating, and strengthened implementation mechanisms to enhance equitable educational access.